Right to the Indian City - Swati Dushyant Sisoudiya; Prof. Ankita Prakash Srivastava; Prof. Varsha Khetrapal, (Indian Journal of Social Science and Literature (IJSSL), 2024)
In Indian governance studies, the urban government is largely understudied. Even less research has been done on it from the standpoint of citizenship and rights. In addition to the general requirement to make the city a more welcoming environment for its inhabitants, the right to the city entails the provision of fundamental urban amenities such as basic housing, clean drinking water, sanitary facilities, and a wide range of other necessities. In urban studies, governance has gotten the least attention, and the current discussion is only about governments in major cities. However, the idea of “right to the city” must be applied to cities of all scales. This paper investigates the significance of and potential applications for the Right to the City in Indian cities. It examines how the Right to the City is expressed internationally in both national and international legal frameworks, recounts Indian housing law precedent, and explains the political strategies of staking claims to urban areas in India. The methodology is based on the literature review, via a critical reading, of the available secondary data. This study analyses the Right to the City to highlight the prevalent issues and challenges in its implementation in India. The study concludes that affirming the right to the city as a basic right arising out of the Indian Constitution would lead to an improvement in urban governance, which would then be carried out in a more inclusive way, taking into consideration the fundamental urban and human rights of its residents and contributing to the larger goal of sustainable cities in India.